Smartchem: An Android Application for Learning Multiple Representations of Acid-Base Chemistry - Eliyawati Eliyawati; Rika Rafikah Agustin; Yustika Sya’bandari; Rossy Andini Herindra Putri (Journal of Science Learning, 2020)
An android application named SmartChem was developed to explain multiple representations of acid-base chemistry. This paper is a description of an android-based media (SmartChem) through the stages of design, development, validation and revision, and finally, limited trials with pre-service science teachers. SmartChem is intended to aid students in understanding through media explanations of symbolic, macroscopic, and submicroscopic representations of acid-base material. The validity of the tool was assessed through the ratings of a panel of five expert judges using Aiken’s validity index (Aiken’s V). The results show that some parts of the SmartChem media needed to be revised, especially in linking submicroscopic level content with symbolism. From the trials of this application with trainee teachers, help in understanding multiple chemical representations of acids and bases was demonstrated; however, the low achievement group was more concerned with technical features, while the higher achieving group appreciated the content and learning experience.